Using developmental evaluation to support knowledge translation: reflections from a large-scale quality improvement project in Indigenous primary healthcare - Alison Laycock; Jodie Bailie; Veronica Matthews; Ross Bailie (BMC, 2019)
Abstract Background Developmental evaluation is a growing area of evaluation practice, advocated for informing the adaptive development of change initiatives in complex social environments. The utilisation focus, complexity perspective and systems thinking of developmental evaluation suggest suitability for evaluating knowledge translation initiatives in primary healthcare. However, there are few examples in the literature to guide its use in these contexts and in Indigenous settings. In this paper, we reflect on our experience of using developmental evaluation to implement a large-scale knowledge translation research project in Australian Aboriginal and Torres Strait Islander primary healthcare. Drawing on principles of knowledge translation and key features of developmental evaluation, we debate the key benefits and challenges of applying this approach to engage diverse stakeholders in using aggregated quality improvement data to identify and address persistent gaps in care delivery. Discussion The developmental evaluation enabled the team to respond to stakeholder feedback and apply learning in real-time to successfully refine theory-informed research and engagement processes, tailor the presentation of findings to stakeholders and context, and support the project's dissemination and knowledge co-production aim. It thereby contributed to the production of robust, useable research findings for informing policy and system change. The use of developmental evaluation appeared to positively influence stakeholders' use of the project reports and their responses to the findings. Challenges included managing a high volume of evaluation data and multiple evaluation purposes, balancing facilitative sense-making processes and change with task-focused project management, and lack of experience in using this evaluation approach. Use of an embedded evaluator with facilitation skills and background knowledge of the project helped to overcome these challenges, as did similarities observed between features of developmental evaluation and continuous quality improvement. Conclusion Our experience of developmental evaluation confirmed our expectations of the potential value of this approach for strengthening improvement interventions and implementation research, and particularly for adapting healthcare innovations in Indigenous settings. In our project, developmental evaluation successfully encompassed evaluation, project adaptation, capacity development and knowledge translation. Further work is warranted to apply this approach more widely to improve primary healthcare initiatives and outcomes, and to evaluate implementation research.